Toxic granulations: a key marker in sepsis - Pandashina Masabanda, Angel Isaias (2025)
Currently, sepsis is considered a potentially life-threatening organ dysfunction that represents an alarming challenge in medical practice, especially in the management of critically ill patients. In this regard, toxic granulations in neutrophils have emerged as an ideal marker to aid in its diagnosis. Therefore, the aim of the study was to analyze the importance of toxic granulations in the diagnosis of sepsis, their prognostic marker potential, and their incorporation into daily clinical practice. A literature review was conducted on studies published between 2019 and 2024 that assessed the relationship between toxic granulations and sepsis. Toxic granulations were associated with a severe inflammatory response, such as sepsis, but have also been observed in other severe infections and some hematological disorders, limiting their utility as a solemarker. In conclusion, toxic granulations are an essential diagnostic, prognostic, and follow-uptool in sepsis, although further research is needed to standardize their use in clinical practice.